Analysis of the Implementation of Re-Thinking Strategic Leadership in MSMEs for Sheet and Bed Cover Products in the City of Bandung - Puspasari, Dewi; Sobandi, Sobandi; Santoso, Budi (West Science Business and Management, 2024)
MSMEs in the bed linen industry often face challenges in increasingly tight market competition and changing consumer dynamics. To remain relevant and competitive in an ever-changing market, MSME leaders need to rethink their leadership strategies. Rethinking in this context includes re-evaluating business models, marketing strategies, production processes, and relationships with customers. MSME leaders need to consider new strategies that enable them to face challenges and exploit opportunities in the bedsheets industry. Based on the results of observations and in-depth interviews with MSME owners who produce bed sheets and bed covers in the Bandung area, it is clear that most of the MSME players who produce bed sheets and bed covers, especially the owners, in this case who are the leaders, have implemented re-thinking strategic leadership, especially those in the bed sheet business who produce on a large scale. . Re-thinking strategic leadership in this case means that MSME bed sheet and bed cover players have re-evaluated business models, marketing strategies, production processes and relationships with customers. MSME owners of bedsheet and bedcover products in Bandung have adopted various strategies to understand and adapt to the rapidly changing business environment. They use e-commerce and social media platforms, prioritize environmentally friendly products, adopt health protocols during the pandemic, and adjust production processes according to environmental regulations. Their strategic leadership drives adaptation through market research, product innovation, sales channel diversification, improved customer service, operational efficiency, collaboration, pricing flexibility, and human resource development. Additionally, they apply long-term thinking through SWOT analysis, market trend monitoring, competitor research, and data analysis. Team collaboration and engagement are also enhanced through cross-functional teams, open communication, shared goals, and collaborative rewards. Technology and innovation are encouraged with training, support systems, feedback loops, and innovation awards. Systemic thinking and leadership development is carried out through outreach, training, open communication, and feedback. These MSMEs also have risk awareness with appropriate risk analysis and risk mitigation as well as regular performance measurements for evaluation and strategy adjustments. MSME leaders are also considering new strategies that will enable them to face challenges and exploit opportunities in the bedsheets industry. MSME leaders in the bed linen industry have implemented strategic leadership to direct their business in a direction that is in line with the company's vision and mission. Strategic leadership involves making smart decisions, identifying market opportunities, managing risks, and developing long-term strategies. Even though the results obtained, not all MSMEs producing bed sheets are as expected.